Analysis of Problem-solving Ability of SDN Dinoyo 3 Malang Students in Inquiry Learning - Yusella, Yeni; Khoiroh, Makrifatul; Setyosari, Punaji; Alfan, Muhammad (KnE Social Sciences, 2023)
This study aims to find out about the role of the scientific inquiry learning model in students’ problem-solving ability in science material for elementary school students. The method used in this research is descriptive qualitative research method. The place for this research is SDN Dinoyo 3 , Malang. The study was carried out on a total of 27e fourth grade students. Data were collected through observation, interviews, and documentation. The data analysis were done using data reduction, data presentation, and data verification. The results of this study indicated that the learning process that applies the scientific inquiry learning model is more efficient for problem-solving ability. Students in the scientific inquiry learning model will play an active role in the process of learning activities, where they are required to be able to solve the given problems. Based on the results of student tests and discussions, it can be concluded that the level of problem-solving ability of students of SDN Dinoyo 3 Malang needs to be improved. Factors that affect students’ problem-solving ability are, students’ lack of accuracy in doing questions, students rarely do questions that are oriented toward problem-solving ability, and lack of mastery of the concept of the topic of hydrology cycle from students. The implications of this study can provide information about the level of students’ problem-solving ability on the indicators displayed. This research is only limited to analysis to determine students’ problem-solving ability, so it is hoped that further research can be carried out which includes the development of learning instruments that can support students’ problem-solving ability. Keywords: problem solving, inquiry, learning, hydrology cycle